Characterization of enzymatically modified rice and barley starches with amylosucrase at scale-up production. (10th July 2015) - Kim, Bum-Su; Kim, Hyun-Seok; Yoo, Sang-Ho
Highlights: Amylosucrase (AS) reaction was performed in a reaction volume 100 times larger than the previously used. Reaction efficiency (RE) of AS was enhanced by the scale up. Elongation of amylopectin branch-chains was achieved as a result of the increased RE. The resistant starch content of Np AS-treated starches was significantly enhanced. Abstract: Physicochemical properties of Neisseria polysaccharea amylosucrase ( Np AS)-treated rice and barley starches were investigated at scale-up production. Pre-gelatinized rice and barley starches were treated with significantly lower Np AS dose (0.1 U/mL) but 100 times larger reaction volume (3500 mL), compared to the analytical scale (35 mL) used in the previous study. Np AS-treated starches in this scale-up production were characterized with respect to reaction efficiency (RE), resistant starch (RS) content, amylopectin (AP) branch-chain length distribution, solubility, swelling power, pasting viscosity, and thermal transition properties. The RE enhanced up to 1.8 times by increasing the reaction volume, which improved the RS content and AP branch-chain lengths of Np AS-treated starches. Compared with the native starch, Np AS-treated starches exhibited lower solubility and swelling power, lower pasting viscosity, and a large increase in the melting peak temperature. Consequently, Np AS treatment of pre-gelatinized starches in this study would be a potential way of replacing commercial RS production.